FENOMENA MAHASISWA KORBAN PERCERAIAN ORANG TUA DI UNIVERSITAS SRIWIJAYA - niswati, Meithesa (Socious Journal, 2024)
This research is entitled "Student Phenomenon of Victims of Parents Divorce at Sriwijaya University". The research problem discusses the implications of parental divorce for social relations, organizational activities, and student learning outcomes at Sriwijaya University. this research aims to analyze and understand the phenomenon of students who are victims of parental divorce at Sriwijaya University. The research method used is descriptive qualitative with a descriptive research strategy. This study uses the Behaviorism theory of John B Watson. Data were obtained through in-depth interviews with 11 informants, documentation, and a literature study. various forms of implications of parental divorce for social relations, organizational activities, and student learning outcomes. The impact of divorce for social relations include (1) promiscuity, (2) Being rude, (3) Losing self-confidence, (4) Self-acceptance, (5) Enjoying life, (6) Embracing, (7) Looking for a good environment, ( 8) Independent, (9) What it is. The implications of divorce for organizational activities include (1) closing oneself, (2) channeling talent, (3) feeling safe, (4) building relationships, (5) seeking experience, and (6) free expression. Meanwhile, the implications of divorce for learning outcomes include (1) High GPA (2) Low GPA (3) Medium GPA.